2015
DOI: 10.1371/journal.pone.0125834
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Expression of Reprimo, a p53-induced Cell Cycle Arrest Gene, Correlates with Invasive Stage of Tumor Progression and p73 Expression in Gastric Cancer

Abstract: Reprimo (RPRM), a downstream effector of p53-induced cell cycle arrest at G2/M, has been proposed as a putative tumor suppressor gene (TSG) and as a potential biomarker for non-invasive detection of gastric cancer (GC). The aim of this study was to evaluate the epigenetic silencing of RPRM gene by promoter methylation and its tumor suppressor function in GC cell lines. Furthermore, clinical significance of RPRM protein product and its association with p53/p73 tumor suppressor protein family was explored. Epige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 21 publications
2
52
1
Order By: Relevance
“…Despite an overall decline in incidence over the last several decades, gastric cancer (GC) remains the fourth most common type of cancer and is the second leading cause of cancerrelated death worldwide (26,27). Although some evidence has been reported, the mechanism of GC is not fully understood (28)(29)(30). Thus, identifying molecular aberrations in GC may improve our understanding of gastric carcinogenesis and help us subdivide patients into biologically and clinically relevant subgroups, as well as develop novel therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an overall decline in incidence over the last several decades, gastric cancer (GC) remains the fourth most common type of cancer and is the second leading cause of cancerrelated death worldwide (26,27). Although some evidence has been reported, the mechanism of GC is not fully understood (28)(29)(30). Thus, identifying molecular aberrations in GC may improve our understanding of gastric carcinogenesis and help us subdivide patients into biologically and clinically relevant subgroups, as well as develop novel therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The RPRM protein is believed to mediate, at least in part, the p53-dependent cell cycle arrest at G2 by the inhibition of Cdc2 activity and nuclear translocation of cyclin B1 (Ohki et al, 2000;Taylor and Stark, 2001). It has also been suggested that RPRM may also be regulated by p73 in an independent manner from p53 in gastric carcinogenesis (Saavedra et al, 2015).The loss of RPRM expression in cancer through abnormal methylation patterns suggests that this gene and its corresponding biochemical pathway might play a role in cancer metabolism and development, and suggests a potential target for treatment against malignancies (Ohki et al, 2000;Wong et al, 2005;Hamilton et al, 2006;Bernal et al, 2008;Luo et al, 2011;Saavedra et al, 2015). To date, efforts to find biomarkers for early stages of cancer have found limited success, and the gene RPRM has emerged as a promising candidate in this area (Bernal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The inverse relationship between methylation and transcription has identified RPRM as a target for aberrant methylation in various cancers, including prostate cancer (Ellinger et al, 2008), lung cancer (Nakajima et al, 2009), hepatocellular carcinoma (Nishida et al, 2008), pancreatic cancer (Sato et al, 2008), head and neck carcinomas (Wong et al, 2005), esophageal cancer (Hamilton et al, 2006) and gastric adenocarcinoma (Bernal et al, 2008;Luo et al, 2011;Saavedra et al, 2015). The abnormal regulation of the genome during cancer is thought to be due to atypical methylation processes rather than the presence of somatic mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Methylation levels were 5.4- to 303-fold higher in H. pylori -positive than in H. pylori -negative subjects ( p < 0.0001) ( Figure 2 ). Schneider et al [ 62 ] performed a quantitative analysis of the DNA methylation status of the promoter region of Reprimo (RPRM), a putative tumor suppressor gene in gastric cancer [ 63 ], which demonstrated an association of the methylation status of the gene with the presence of virulence factors in the infecting H. pylori strains. Taken together, these findings suggest that H. pylori infection potently induces aberrant DNA methylation.…”
Section: Dna Methylation In Regulatory Regions Of Protein-coding Tmentioning
confidence: 99%
“…An emerging body of evidence suggests that DNA methylation may be used as novel and specific biomarkers in gastric cancer [ 65 , 66 ] through the measurement of circulating DNA in serum (cell-free DNA (cfDNA)). In this scenario, we have discovered that RPRM displays differences in methylation levels between nontumor adjacent mucosa (NTAM) and cancer tissue samples ( Figure 3(a) ) [ 63 ]. Methylation status of this gene may be assessed in plasma samples ( Figure 3(b) ) [ 67 , 68 ], offering the opportunity for noninvasive detection of gastric cancer.…”
Section: Dna Methylation In Regulatory Regions Of Protein-coding Tmentioning
confidence: 99%